2012
DOI: 10.2480/agrmet.68.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced annual litterfall production due to spring solar radiation in cool-temperate mixed forests of northern Hokkaido, Japan

Abstract: We determined the interannual variation of annual litterfall rate in cool-temperate forests [three mixed-forests (Mx1-Mx3), an evergreen coniferous forest (Ec), and a deciduous conifer plantation (Dc)] of northern Hokkaido over a 16-year observation period (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) and evaluated the effect of meteorological and phenological variables on the annual litterfall production. Total solar radiation during spring (from March to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…The litterfall peak patterns (i.e., spring and fall) observed in CS and SH b stands may be due to two factors, namely, (1) the influence of temperature on leaf phenology of the species, and (2) the disturbance effect of typhoons. First, it was reported that the enhanced annual litterfall production was positively related to temperature due to the advancement of leaf expansion and increased forest productivity during the spring season [50][51][52][53]. The litterfall peaks we observed are also consistent with the pattern reported for a subtropical evergreen forest in China [54], which was associated with physiological leaf senescence as cited in similar studies [55,56].…”
Section: Litterfall Production In Different Forestssupporting
confidence: 90%
“…The litterfall peak patterns (i.e., spring and fall) observed in CS and SH b stands may be due to two factors, namely, (1) the influence of temperature on leaf phenology of the species, and (2) the disturbance effect of typhoons. First, it was reported that the enhanced annual litterfall production was positively related to temperature due to the advancement of leaf expansion and increased forest productivity during the spring season [50][51][52][53]. The litterfall peaks we observed are also consistent with the pattern reported for a subtropical evergreen forest in China [54], which was associated with physiological leaf senescence as cited in similar studies [55,56].…”
Section: Litterfall Production In Different Forestssupporting
confidence: 90%
“…Our use of 20 × 20 m treatment area was, to our knowledge, the largest spatial scale utilized to date for advancing snowmelt treatment in an experiment like this. The lack of the significant decrease of water availability could be partly due to the humid climate in northern Hokkaido where water is unlikely to be a limiting resource for plants (Aguilos et al, 2012). Blankinship et al (2014) conducted a 4 × 4 m delayed‐snowmelt manipulation that induced an increase in water availability at the surface soil of a temperate forest in the Sierra Nevada Mountains of California, which experiences a Mediterranean‐type climate with water being a primary limiting resource for plants.…”
Section: Discussionmentioning
confidence: 99%
“…When we decided upon the scenario to mimic in the present study, we examined the data of the average spring (March-May) air temperature and the date of snowmelt from 1996 to 2014 in northern Hokkaido, which had partly been reported in Aguilos et al (2012) (Appendix S1: Figure S1). While the average date of snow disappearance during the monitoring period was DOY 111, that with extremely warm temperatures at the end of spring was DOY 96.…”
Section: Experimental Designmentioning
confidence: 99%
“…归还到地表的所有有机物质的总称, 是连接陆地生 态系统地下和地上生态过程的关键媒介 (Facelli & Pickett, 1991) (Janssens & Pilegaard, 2003;DeForest et al, 2009)。 总的来说, 凋落物产量的时间动态由多种外部 因素以及物种生理特征所决定。长期定位观测发现 群落特征是影响凋落物年际动态的主要因素 (官丽 莉等, 2004;Li et al, 2010;Aguilos et al, 2012)。 降水 量及温度是影响凋落物季节动态的主要因素 (Sanches et al, 2008;张新平等, 2008;武启骞等, 2017 图4 2008-2015年8个气候变量月值的主成分分析结果。每 个点的横纵坐标为该变量在主成分轴上的荷载值, 百分数 表示方差被该主成分轴所解释的部分。"prep"表示月降水量, "temp" "max temp" "min temp"分别表示月平均气温、月最高 气温及月最低气温。 Fig. 4 Principal component analysis of the monthly values for eight meteorological variables from January 2008 to December 2015.…”
Section: 凋落物也称枯落物 是指植物地上部分产生并unclassified